Mobile devices and learning: Student perspectives and inclination at South African higher learning institutions - Wiid, Johannes A.; Cant, Michael C. (Universitas Negeri Semarang, 2024)
The increasing use of mobile devices in business extends to academia, posing challenges for educators amid the dynamic landscape of teaching and learning methods. Educators must adapt to these changes to meet students' technology-driven learning needs. This study investigated students' perspectives on mobile device usage and their inclination to integrate the use of mobile devices into learning activities. In a self-administered LimeSurvey questionnaire, students demonstrated a positive attitude towards mobile device use in learning and expressed optimism about its future potential. Exploratory factor analysis identified three key factors that influence mobile device selection for learning: behavioural lifestyle intentions, subjective social norms, and attitude and expectations. A multiple linear regression analysis revealed that these factors are predictors of the use of mobile devices for study and learning purposes. Institutions and educators should leverage these insights to enable students to acquire mobile devices, either as part of study material or through loan schemes or financial assistance.